2022
DOI: 10.14256/jce.3358.2021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recycled PET and TEOA on performance characteristics of bitumen

Abstract: In this study, the recycled PET is used in bitumen modification by applying a different process in order to eliminate the phase separation problem. For this purpose, modified bitumens are obtained by adding the triethanolamine (TEOA) chemical (wt. 2.5 %) and PET (wt. 2, 4, 6, 8, 10 %) to pure bitumen. The properties of modified bitumens are determined by chemical, physical, and rheological tests. According to the test results, bitumen reacts with PET, and 6 % PET ratio is a critical value. At this ratio, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…However, regarding the material quality, an increase in the plastomer content resulted in a successive reduction in the bitumen resistance to low temperatures. Similar results were obtained by the authors of study [29], where it was demonstrated that a PET content increase to a level of 6% and enrichment with a compatibilizer does not imply any deterioration of the low-temperature properties of bitumen.…”
Section: Modelling Of Bitumen Properties Using a Generalised Linear M...supporting
confidence: 89%
See 1 more Smart Citation
“…However, regarding the material quality, an increase in the plastomer content resulted in a successive reduction in the bitumen resistance to low temperatures. Similar results were obtained by the authors of study [29], where it was demonstrated that a PET content increase to a level of 6% and enrichment with a compatibilizer does not imply any deterioration of the low-temperature properties of bitumen.…”
Section: Modelling Of Bitumen Properties Using a Generalised Linear M...supporting
confidence: 89%
“…An increase in the PET content improves the stiffness and viscosity of bitumen and bituminous mixes [27,28]. Studies on PET implementation showed no evident mix stability losses or adverse impacts on the BBR critical temperature when the PET content was up to 6% [29].…”
Section: Introductionmentioning
confidence: 98%
“…ASTM D7175) by determining complex shear modulus (|G*|) defined as a measure of the binder's total resistance to deformation upon shear stress, and phase angle (δ) being an indicator of relative viscous and elastic deformation of the binder. By measuring these parameters, the rutting and fatigue performance of the binders can be determined [30,38]. According to the Superpave criterion outline in AASHTO M320 [39], the rutting factor (|G*|/sin(δ)) represented the high-temperature viscous component of the total bitumen stiffness and, following the standard, must reach a minimum of 1 kPa for the original binder to estimate the high-temperature Performance Grade (PG up ) of the analyzed sample.…”
Section: Methods Of Polymer-modified Bitumen Characterizationmentioning
confidence: 99%